An integral system for assisted mobility [automated wheelchair]. - Mazo, M. (IEEE Robotics and automation magazine)
The modularity of the electronic guidance systems of the SIAMO wheelchair allows for user-specific adaptability based on environment and degree of handicap. The overall system includes an innovative user-machine interface, a complete sensory subsystem (ultrasonic, infrared, vision, etc), and an advanced strategy of control and navigation. This allows different alternatives for guidance and guarantees user safety and comfort